[Comment on Tobin]: Rejoinder - Tobin, James (Quarterly Journal of Economics, 1970)
Journal Article Rejoinder Get access James Tobin James Tobin Yale University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 84, Issue 2, May 1970, Pages 328–329, https://doi.org/10.2307/1883018 Published: 01 May 1970